Modernization of the Peruvian Armed Forces: Organization and Design of the Force - O'Connor Riglos, Luis Ivan (2020)
This study has been carried out in order to internalize the process of modernization of the Armed Forces by analyzing its organization and the design of its forces. The research carried out was of a theoretical-empirical type, with a qualitative approach, since the objective of the aforementioned was intended to describe the organization and design of the force in the Peruvian Army, in its modernization process, 2002-2018, for which which the documentary investigation information technique was used. When carrying out the bibliographic review based on the objectives, it was found that the modernization process depends directly and in order of precedence on the organization of the force and its design; having to attend to each of the needs and responsibilities of the Forces, since at present, the orientation of the modernization processes must be closely linked to threats against national security; since the globalized world presents new threats that evolve together according to the circumstances. Finally, it was concluded that, regarding the organization and design of the force, the Strategic Axes of Action must be attended, the same ones that constitute the main lines for the modernization of the Armed Forces and the achievement of the objectives , since these Strategic Axes ensure the development of the Armed Forces into the future, being the same the organization, defense policies, military cooperation, humanitarian actions and peace operations, education and training, defense industry and technology.